Hinged Fibulae from Halae in the Collection of the National Archaeological Museum of Athens - Agata Kubala (Ksiegarnia Akademicka Publishing, 2019)
The National Archaeological Museum of Athens possesses fourteen Greek fibulae of different sizes found during American excavations at Halae of Locris carried out between 1911 and 1914. They belong to the hinged fibula group, which is characterized by the distinctive decoration of its bows. Fibulae of this type have been found in the area of the Central Balkans, Romania, and northern and central Greece. Observable differences in the shapes of the decorative elements of these fibulae are of regional nature and allow several varieties to be identified within the type. The fibulae in question represent a local transformation of the northern models manifested mainly in the use of native Greek patterns particularly in the case of the palmettes decorating their hinge plates which are purely Greek in shape, and in the form of projections adorning their bows. The high artistic quality of the Halae fibulae reinforces the conviction of their Greek workmanship. They differ from each other in details, and this makes them very good examples of the development of the Greek variant of the hinged type fibula in the 5th century BC.